The relationship between previous viral infections and the pathophysiology of guillain-barré syndrome: A systematic review and meta-analysis (Research, Society and Development, 2026)
Objective: To analyse the relationship between Guillain-Barré syndrome (GBS) and viral infections, including SARS-CoV-2, as well as post-vaccination events, with a focus on pathophysiological, clinical and therapeutic aspects. Method: This is a systematic review of the literature, conducted in accordance with the PRISMA guidelines, involving a search of scientific databases, including studies published between 2014 and 2025. Controlled search terms and predefined inclusion and exclusion criteria were used, resulting in the final selection of 10 articles. Results and discussion: The findings show that GBS is frequently associated with autoimmune mechanisms triggered by viral infections and, less commonly, by vaccination. Diversity in clinical presentation was observed, with a predominance of ascending muscle weakness, areflexia and possible respiratory compromise. Studies also highlight the role of molecular mimicry in the pathophysiology of the disease. Conclusion: It is concluded that early identification of GBS is fundamental for appropriate clinical management and reduction of complications. Furthermore, the importance of epidemiological surveillance and the continuation of studies evaluating vaccine safety and the immunological mechanisms involved is emphasised.